When a spring mass system is connected vertically with two massless springs in series whose spring constants are $k_1$ and $k_2$ to a block of mass $m$ we know that equal forces act on both the springs. Let that force during oscillations be $F$.

When we calculate effective spring constant $k_s$, why don't we say the net force acting on the system is $2F$?

Finding net force acting on the above system:

When the block is attached,the system attains equilibrium position through displacements $x'_1$ and $x'_2$.

At equilibrium: $2F'=mg$(Where $F'$ is magnitude of spring force initially by each spring)

So, $k_1x'_1+k_2x'_2=mg$ (equation 1)

When the system is pulled down it makes oscillations,now:

Total elongation be $x$

Elongation in spring 1 be $x_1$ and elongation in spring 2 be $x_2$.

Total spring force $= -k_1x'_1-k_2x'_2-k_1x_1-k_2x_2$

Total forces acting on the system $= -k_1x'_1-k_2x'_2-k_1x_1-k_2x_2+mg = -mg-k_1x_1-k_2x_2+mg$
(from equation 1)

So, total force $= -k_1x_1-k_2x_2 = F_1+F_2=2F$(as we know that both forces are equal)

So net force acting on the system is $2F$

The way I calculated effective spring constant is:


$2F/k_s = F/k_1 + F/k_2$

$2/k _s = 1/k_1 +1/k_2$

But that is not a correct equation. What's wrong in taking net force acting on system as $2F$.


3 Answers 3


When the springs (assumed to be massless) are hung upside down, they will have a zero extension. So in fact $$mg = k_1x+k_2x$$ when the mass is added to the system.

You wrote that the resultant force $$F_r = F_1+F_2$$ and concluded that this should be $2F$ as if the force in both springs were equal.

So what you should have done is write the resultant displacement $$x=x_1+x_2$$ so that $$\frac{mg}{k_s}=\frac{mg}{k_1}+\frac{mg}{k_2}$$ where $k_s$ is a effective spring constant. This will then give $$k_s=(\frac{1}{k_1}+\frac{1}{k_2})^{-1}$$


The springs are massless, so the tension at any point in either spring is the same value, $F$. For the two individual springs, with extensions $x_1$ and $x_2$, we have#

$F = k_1x_1=k_2x_2$

and when considered as a single spring they have an effective spring constant $k$ such that

$F = k(x_1+x_2) \\\displaystyle \Rightarrow F = k\left(\frac F {k_1} + \frac F {k_2} \right) \\\displaystyle \Rightarrow \frac 1 k = \frac 1 {k_1} + \frac 1 {k_2} $

Note that if we join two identical springs in series (so $k_1=k_2$ and $x_1=x_2$) then the spring constant of the joint spring is only half that of its two components. This is because it produces the same force $F$ with twice the extension of the individual springs, since $x=2x_1$.


ok so the first condition for the series spring system is : The spring force in the entire system is the same i.e the tension in the springs is the same


where $k_e$ is the equivalent spring constant

so if the system is vertical let gravitation force, mg, be $F$

hence $x_1=F/k_1$ ,$x_2=F/k_2$ and $x_1+x_2=F/k_e$


$\Rightarrow 1/k_e=1/k_1+1/k_2$

Now let's deal with your question, So I recommend You look into the free body diagram again. The tension in the entire system is equal to $F$

If u are facing troubles you can also try relating this with electricity resistor circuits. In a series connection, the current is the same through the resistors similarly in a series spring connection the tension is the same throughout. And in the case of a parallel connection the current splits in the branches but with each branch having the same potential difference, similarly, in a parallel spring system the two springs experience different tensions but extend/ contract equally

For further reference: I have some trouble with springs in series



  • $\begingroup$ Can you attach a free body diagram of the above case representing all the forces acting on the system? $\endgroup$
    – Stein
    Commented Apr 4, 2021 at 7:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.